Well-Being of Individuals With Late-Deafness. - Meyer, Jill M.; Kashubeck-West, Susan (Rehabilitation Psychology, 2013)
Objective: The purpose of this study was to examine the relationships between disability factors and psychosocial outcomes in a sample of individuals with acquired hearing loss, specifically late-deafness (loss after age 12). Method: Participants (N = 277) completed the following measures at a single point in time: the Hearing Handicap Inventory for Adults, the Reactions to Impairment and Disability Inventory, the Ways of Coping Questionnaire, the Psychological Weil-Being scale, and a demographic questionnaire. Structural equation modeling was conducted to determine whether coping style mediated the relationships between disability factors (i.e., age of onset, perceived severity of disability, and perceived adaptation to disability) and psychological well-being. Results: Emotion-focused coping partially mediated the relationships between perceived severity of hearing loss and psychological well-being, and between perceived adaptation to disability and psychological well-being (B = - .36), and problem-focused coping partially mediated the relationship between perceived adaptation to disability and psychological well-being (B = .49). The model was a good fit for these data (comparative fit index and incremental fit index = .94; Tucker-Lewis index = .92; root mean square error of approximation = .09). Conclusion: Perceived adaptation to disability and perceived severity of disability acted as direct predictors of psychological well-being, and as indirect predictors through their relationship with coping. Implications for the process of adaptation and counseling for individuals with acquired hearing loss are discussed.